2017
DOI: 10.1016/j.jmb.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

RNA Exosome and Non-coding RNA-Coupled Mechanisms in AID-Mediated Genomic Alterations

Abstract: The eukaryotic RNA exosome is a well-conserved protein complex with ribonuclease activity implicated in RNA metabolism. Various families of non-coding RNAs (ncRNAs) have been identified as substrates of the complex, underscoring its role as a ncRNA processing/degradation unit. However, the role of RNA exosome and its RNA processing activity on DNA mutagenesis/alteration events have not been investigated until recently. B lymphocytes use two DNA alteration mechanisms, class switch recombination (CSR) and somati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 124 publications
(123 reference statements)
1
13
0
1
Order By: Relevance
“…Over the last decade, the concept has emerged that exosome-mediated R-loop prevention is a critical step in immunoglobulin class switch recombination (CSR) and somatic hypermutation (SHM) in B lymphocytes [ 171 ]. To initiate CSR and SHM, activation-induced cytidine deaminase (AID) deaminates cytidines on both template and non-template DNA strands of transcribing switch regions.…”
Section: Significance Of the Nuclear Rna Exosome In Mammalian Biolmentioning
confidence: 99%
“…Over the last decade, the concept has emerged that exosome-mediated R-loop prevention is a critical step in immunoglobulin class switch recombination (CSR) and somatic hypermutation (SHM) in B lymphocytes [ 171 ]. To initiate CSR and SHM, activation-induced cytidine deaminase (AID) deaminates cytidines on both template and non-template DNA strands of transcribing switch regions.…”
Section: Significance Of the Nuclear Rna Exosome In Mammalian Biolmentioning
confidence: 99%
“…10,11 As the main information molecules in exosomes, non-coding RNAs are primary mediators of the functions of exosomes. 12 However, the role of chondrosarcoma cell-derived exosomes in the progression of chondrosarcoma remains unelucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the elongation-competent RNA polymerase II complex, when transcriptionally stalled at the IgH switch sequence (IgS), recruits AID using the RNA processing activity of the 3 0 -5 0 noncoding RNA exonuclease RNA exosome complex (Basu et al, 2011;Pavri et al, 2010;Pavri and Nussenzweig, 2011;Rajagopal et al, 2009;Wang et al, 2009). AID and RNA exosome directly interact with each other, providing evidence for ncRNA-processing-mediated targeting of AID to its physiological DNA substrates (Basu et al, 2011;Chandra et al, 2015;Laffleur et al, 2017). Another observation is the role of RNA exosome in providing AID access to the template DNA of the IgS (switch) regions.…”
Section: Introductionmentioning
confidence: 99%